Optimasi Inventori Material Bubuk Nylon pada Proses Coating dengan Pendekatan Probabilistik - Yevita Nursyanti; Selly Octaviani (Universitas Bunda Mulia, 2021)
This research aims to optimize the supply of raw material for nylon powder for the manufacturing industry. The problem was found in the nylon powder warehouse which was out of stock so that it had to be replaced with plastic raw materials to keep the production process running. The change of raw material from nylon powder to plasco was done because the company did not make an emergency order for nylon powder. This is due to the high cost of emergency orders. The use of plasco powder makes the company accept a sizeable return of goods. Therefore it is necessary to do a good inventory management to overcome the out of stock. The method used to solve this problem is the probabilistic P back order model. Demand in the previous period was normally distributed. The results of processing with the P back order model produce a service level of 99.95%. It is hoped that the company will not experience out of stock again. In addition, a savings of 4.50% were obtained from the total costs incurred by the company. Inventory policy obtained using the P back order model with an order time of (T) 0.358 or for 130 days a new order will be made, and the total inventory cost is Rp.418,363,268 / year with a service level of 99.995%.